Analysis of ferroresonance effect in power transformer - Zulkifli, Mardzulliana; Abu Bakar, Abdul Halim; Sahari, Norain; Mohd Noh, Faridah Hanim; Zambri, Nor Aira; Mustafa, Farahiyah (FAZ Publishing, 2020)
Ferroresonance phenomenon normally might occur in circuit that contains non-linear inductances, capacities, voltage source and small losses. The formation of Ferroresonance effect and Ferroresonance overvoltage become more topical problem today. Then by lowering of power losses during electric power transmission, system might become more sensitive on the consequences of different transient progresses. It is important to give an appropriate extra attention to the analysis and outline of simulation with the usage the most accurate mathematical models, which allow us to study the behavior of ferroresonance circuit without any risk. This paper shows a development effort to study and assess various impacts of ferroresonance phenomenon on operating performance of power transformers and to investigate ways to mitigate the effects of such phenomenon. This study used three-phase core type of transformer. The example of formation and process of ferroresonance effect in the part of power system and use of simulative software PSCAD will be described in detail in this thesis. The results of the technical investigation and the associated ferroresonance simulation work by PSCAD showed that ferroresonance can cause dangerous overvoltages and overcurrents in three-phase core type transformers.